THE LIGHTWEIGHT TEXTILE REINFORCED CONCRETE FOR THIN-WALLED STRUCTURES - Tereza Cibulka; Luboš Musil; Jan Vodička (Acta Polytechnica CTU Proceedings, 2019)
The article deals with lightweight concrete with non-conventional reinforcement and its application in thin-walled structures. As part of experimental research, several sets of thin-walled slab and complementary specimen were made to determine the material characteristics of lightweight concrete. The porous aggregate Liapor was used in the recipe. Two-dimensional carbon and 3D glass textiles were used as reinforcement. The impact study of different casting technologies and recipe on the material characteristics of lightweight concrete was included in the research. Fresh concrete for the slab production was placed in special wooden molds. The slabs were concreted in vertical and horizontal position. The casting method has a significant impact on the element material characteristics. Reinforced specimens have shown high strength, even in thin-walled structures with low bulk density.